Factors Affecting Customers Online Search Intention and Online Purchase Intention using Social Networks: Case Study of Online Shop on Instagram - Putri, Jessica Wongso (iBuss Management, 2015)
As the internet usage in Indonesia keep growing rapidly, it creates big opportunities for apparel online shops owner to market their products through many popular online media, especially Instagram. However, many online shop owners have no clue how to market their apparel product effectively via Instagram. Therefore, this research created to analyze the factors that can influence the customersâ purchase intention. Â Those factors are Utilitarian Value of Internet Information Search, Hedonic Value of Internet Information Search, Perceived Benefits of Internet Shopping, Perceived Risk of Internet Shopping, and Online Purchase Experience as the predictors. In addition, realizing the importance of information search as main consideration in purchasing decision, researcher also analyze the use of Online Search Intention as the mediating variable between this relationship.This research conducted by spread questionnaires to 114 apparel online shoppers and analyzed using Path and Sobel analysis. The result of this research shows only Utilitarian Value of Internet Information Search, Hedonic Value of Internet Information Search, and Online Purchase Experience are significant predictors of Online Purchase Intention. In addition, the Sobel test showed that Online Search Intention is not a significant mediating variable in this research.Keywords: Utilitarian Value, Hedonic Value, Perceived Benefit, Perceived Risk, and Purchase Experience